How to create an optopia? - Kim Stanley Robinson's "Ministry for the future" and the politics of hope - Mikes, A; New, S (SAGE Publications, 2023)
Kim Stanley Robinson—award-winning science fiction writer—has warned us that our current history is a choice between utopia or catastrophe. In this interview and in the following reflections, we explore the implications of this existential choice for the social science disciplines; in particular, economics, finance, accounting, and management. Our goals are to build a provocation and develop some propositions about the direction of capitalism and the purpose of management research in an age of climate crisis. Against the backdrop of dread and greed and the specter of plutocratic capitalism, we offer a politics of hope. We envision a green capitalism in which corporations are held accountable for environmental and social stewardship. Rather than falling back on government or the corporation as an “either/or” choice, we urge a “both/and” approach and call for the active inclusion of communities and citizens in climate response through democratic, polycentric governance structures. Within this agenda, we envision a new role for the academy as “Ministry”; namely, giving voice to future generations and the silent (or silenced) victims of the present and, by embracing pragmatic realism, inspiring a liveable future—an optopia—that we can still forge from where we are.